Serological and vaccine evaluation for hepatitis B among Community Health Workers - Tauana de Souza Amaral; Clery Mariano da Silva Alves; Fabiana Ribeiro Rezende; Karlla Antonieta Amorim Caetano; Anaclara Ferreira Veiga Tipple (Universidade de São Paulo, 2023)
Abstract Objective: to identify the vaccination and serological status against hepatitis B among community health workers; to vaccinate against hepatitis B virus and to evaluate the immune response of susceptible workers. Method: phase I, cross-sectional and descriptive study, among community health workers in a capital city of the Midwest region, through a self-administered questionnaire, checking of vaccination cards, and blood collection for testing of serological markers for hepatitis B. Phase II, cohort study carried out in vaccinated non-immune workers identified in phase I. They received one dose of vaccine (challenge dose) and serological testing. Results: a total of 109 workers participated in the study. Most had vaccination record (97; 89.0%) and vaccination completeness (75; 77.3%), while the isolated anti-HBs (Antibodies against hepatitis B virus) marker was detected in 78 (71.6%) workers. The prevalence of hepatitis B virus exposure was 8.2%. Of the ten non-immune vaccinated workers, after challenge dose, one remained susceptible. Conclusion: although most workers are vaccinated and show immunological response to hepatitis B, susceptibility after challenge dose was identified. Therefore, it is necessary to have a surveillance program of the vaccination situation and serological status for this virus, to promote these workers' safety.